Impact of Anonymity Broker ID on Market Quality: Evidence From Indonesia Stock Exchange - Farah Permanasari; Buddi Wibowo (Syntax Literate, 2023)
This study aims to determine the effect of the implementation of Anonymity Broker ID on the quality of the stock market on the Indonesia Stock Exchange (IDX). The application of Anonymity Broker ID is measured by dummy indicators over the period before and after Anonymity Broker ID. Market quality measurement consists of high low volatility of stocks, bid-ask-spread, total depth value and volume. Hypothesis testing was carried out using Fixed Effect Ordinary Least Squares (OLS) and Fixed Effect Two-Stage Least Square (2SLS) regression models and using a sample of all stocks that were actively transacting during the period 04 December 2020 to 06 December 2022. The results provide empirical evidence that Anonymity Broker ID has a positive effect on the volatility of the 330 most active stocks, positively affects Total Depth Value, Bid Ask Spread and Volume. It can generally be concluded that Anonymity Broker ID can effectively dampen excessive market reaction during enactment.